How the EU really works - Costa, Olivier; Brack, Nathalie 1984- (Routledge, 2016)
The European Union is facing a profound crisis and is confronted with multiple challenges. Over the last two decades, it has experienced a series of dramatic changes to its powers, its institutional design, its constitutional framework and its borders. At the same time, the uneasy relationship between European citizens and elites has complicated both the reform and the function of the Union. While the Lisbon treaty provided some answers to crucial questions, it did not clarify the nature of the EU, which remains at the crossroads of federal and intergovernmental logic. The current economic and financial crisis puts the EU's legitimacy further under pressure and creates the impression of a turning point. This book provides a concise analysis of the EU and its dynamics by paying particular attention to its day to day operation. It aims to help students and scholars understand its evolution, its institutions, its decision-making and the interactions between the EU and various actors. Avoiding abstract theorizing, the authors propose an easy to read analysis of how the Union works while recognizing the complexity of the situation. Throughout the book, the key issues of European integration are addressed: democratic deficit, politicization, the role of member states, institutional crisis and citizen involvement.